Anterior Lumbar Interbody Fusion Integrated Screw Cages: Intrinsic Load Generation, Subsidence, and Torsional Stability. Issue 2 (9th January 2017) - Assem, Yusuf; Pelletier, Matthew H.; Mobbs, Ralph J.; Phan, Kevin; Walsh, William R.
Abstract : Objective: To perform a repeatable idealized in vitro model to evaluate the effects of key design features and integrated screw fixation on unloaded surface engagement, subsidence, and torsional stability. Methods: We evaluated four different stand‐alone anterior lumbar interbody fusion (ALIF) cages with two, three, and four screw designs. Polyurethane (saw‐bone) foam blocks were used to simulate the vertebral bone. Fuji Film was used to measure the contact footprint, average pressure, and load generated by fixating the cages with screws. Subsidence was tested by axially loading the constructs at 10 N/s to 400 N and torsional load was applied +/−1 Nm for 10 cycles to assess stability. Outcome measures included total subsidence and maximal torsional angle range. Results: Cages 1, 2, and 4 were symmetrical and produced similar results in terms of contact footprint, average pressure, and load. The addition of integrated screws into the cage‐bone block construct demonstrated a clear trend towards decreased subsidence. Cage 2 with surface titanium angled ridges and a keel produced the greatest subsidence with and without screws, significantly more than all other cages ( P < 0.05). Angular rotation was not significantly affected by the addition of screws ( P < 0.066). A statistically significant correlation existed between subsidence and reduced angular rotation across all cage constructs ( P = 0.018). Conclusion: Each stand‐alone cage featured unique surface characteristics, which resulted in differing cage–foam interface engagement, influencing the subsidence and torsional angle. Increased subsidence significantly reduced the torsional angle across all cage constructs.